2011
DOI: 10.1111/j.1540-8175.2010.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Perforation, the Most Feared Complication of TEE: Early Recognition by Multimodality Imaging

Abstract: Esophageal perforation is the most feared complication of transesophageal echocardiography (TEE), although the overall risk is extremely low. We report a case of esophageal perforation in a 77-year-old woman who had no apparent contraindications to TEE. Chronic steroid therapy for symptoms of asthma as well as osteophytic changes of the cervical vertebrae contributed to her increased risk of perforation. Unlike in prior reports, the perforation in this case was fortuitously recognized rapidly due to ingestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 6 publications
0
28
0
2
Order By: Relevance
“…Other authors have suggested up-front multi-modal imaging to guide diagnosis and treatment [19]. In the current study, the single most predictive imaging finding was the presence of a retropharyngeal fluid collection.…”
Section: Commentmentioning
confidence: 74%
“…Other authors have suggested up-front multi-modal imaging to guide diagnosis and treatment [19]. In the current study, the single most predictive imaging finding was the presence of a retropharyngeal fluid collection.…”
Section: Commentmentioning
confidence: 74%
“…All lesions resulting from dilatation, mucosectomy and rigid endoscopy healed sustainably after stenting. Lesions after TEE are typically located in the cervical esophagus [15] and are best treated by over-sewing and drainage [16]. 5 lesions (two distal, two in the thoracic part, and only one in the cervical esophagus) of this type in our sample were treated in 60% (3/5) successfully by one single stent.…”
Section: Discussionmentioning
confidence: 85%
“…The most commonly reported complications of TEE (such as lip injury and hoarseness) do not usually require significant medical intervention . Thankfully, life‐threatening complications are rare, with the incidence of esophageal perforation reported to be 0.01–0.09% . The mechanism of esophageal injury during a TEE examination is thought to be a combination of thermal energy from the probe tip and direct trauma and pressure during probe insertion, manipulation, and removal …”
Section: Discussionmentioning
confidence: 99%